A Citizen Science Project: Associations of the Oral Microbiota with Body Mass Index and Measures of Sweet Taste Liking (P20-030-19). (13th June 2019) - Bu, Sihan; Sugino, Kameron; Garneau, Nicole; Nuessle, Tiffany; Tucker, Robin; Comstock, Sarah
Abstract: Objectives: To determine if the oral microbiota is associated with body mass index (BMI) in adults. To determine if sweet taste liking measures are associated with the composition of the oral microbiota in either adults or children. Methods: Participants ages 8 + years were recruited from visitors to the Denver Museum of Nature & Science. Participants sampled five concentrations of sucrose (0.0%, 2.4%, 4.3%, 7.7%, 13.7% w/v) by swishing and spitting 5 mL of each. Sweet taste liking for each solution was measured using a 100 mm visual analog scale (VAS) with the anchors: 'dislike extremely' and 'like extremely.'Participants used swabs to collect oral microbiota samples. DNA was extracted from these samples, 16S rRNA libraries were made, and the resulting libraries were sequenced. Height and weight were measured at the museum by trained staff. Results: Overall, as adult body mass index (BMI) increased, alpha diversity (Chao1) of the adult oral microbiota decreased. The adult oral microbiota differed in membership. Underweight and normal weight participants had different oral microbiota communities than overweight and obese participants. These associations remained significant when females were analyzed as a separate group, but not when males were analyzed as a separate group. The differences were based on the types of bacteria present but not the abundance of those bacteria. Oral microbiota of underweight and normal weight participants were defined by the presence of Corynebacterium, Bacillus, and unclassified Clostridiales . With respect to sweet liking, alpha diversity (Chao1) was positively associated with liking of the 2.4% sucrose solution (tertiles) in female adults and female children. Conclusions: Oral microbiota community structure is associated with adult BMI. Furthermore, the level of liking of sweet solutions in both adults and children is associated with alpha diversity of the oral microbiota. Funding Sources: The Sweet-Tasting Study in the Genetics of Taste Lab was supported by both the Denver Museum of Nature & Science and the Denver Museum of Nature & Science Foundation. This work was also supported by the USDA National Institute of Food and Agriculture and Michigan State AgBioResearch.